MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 015 BERINGIN JAYA KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Purwanto Purwanto (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low learning outcomes of science in grade V 015 SD Negeri Beringin Jaya.This study aims to improve the learning process to improve student learning outcomes. This research is aclassroom action research conducted at 015 Beringin Jaya Elementary School. The data used in this study aredata on teacher and student activity and student learning outcomes. The results obtained from the data were theteacher activity in the first cycle of the first meeting with a percentage of 52.5%, the second meeting with apercentage of 70.5%, in the second cycle at the third meeting the percentage of 80%, and at the meeting 4percentage obtained 91.5%. The observation data of students in this study obtained the percentage of the firstcycle of the 1st meeting was 57%, the second meeting was 73.5%, in the second cycle the third meeting was85%, and the fourth meeting was 96%. prove that student activity has increased. Data on the improvement ofstudent learning outcomes in class V SDN 015 Beringin Jaya District Sigingi Hilir in the initial data obtained anaverage of 63.5, in daily tests I obtained an average class of 72, and on the daily test II obtained an average of79 prove that the use of direct learning methods in science learning is effectively used in class V.